2021
DOI: 10.29227/im-2019-01-26
|View full text |Cite
|
Sign up to set email alerts
|

Beneficiation of Talc-Magnesite Ore with Cu-Co Mineralization

Abstract: Magnesite ore with a low chalcopyrite – cobaltite mineralization was subjected to a series of separations designed to evaluate thepossible concentration of the two accessory minerals. Although the Cu-Co grade in the ore (> 0.01% Co, > 0.1% Cu) is significantlylower than the typical economic grades, content of the main valuable mineral for which the ore is mined and processed incombination with a listing of cobalt as a critical raw material, coupled with their higher price might compensate for the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has been previously shown that the presence of very fine particles has a negative effect on the concentrate grade due to the entrainment effect [4,30,31] and possibly also because of the formation of slime mineral coatings on surfaces of talc particles [22,23]. To minimize the influence of the entrainment effect on the results of the flotation tests, two approaches were used as follows: rather extensive use of screening or sieving during the comminution stage and froth washing during flotation tests [21]. Removal of fine particles prior to the next comminution stage is a common practice used to prevent overgrinding of the ore. We were thus able to achieve d80 = 150 µm with only about 20% of particles below 25 µm, which are most likely to be recovered by the entrainment effect [30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously shown that the presence of very fine particles has a negative effect on the concentrate grade due to the entrainment effect [4,30,31] and possibly also because of the formation of slime mineral coatings on surfaces of talc particles [22,23]. To minimize the influence of the entrainment effect on the results of the flotation tests, two approaches were used as follows: rather extensive use of screening or sieving during the comminution stage and froth washing during flotation tests [21]. Removal of fine particles prior to the next comminution stage is a common practice used to prevent overgrinding of the ore. We were thus able to achieve d80 = 150 µm with only about 20% of particles below 25 µm, which are most likely to be recovered by the entrainment effect [30].…”
Section: Resultsmentioning
confidence: 99%
“…From the measured weight of the four obtained products, first individual and then cumulative yields (γ) were calculated. Results of the grade analyses and calculated yields were then used to calculate the cumulative product grade (c) in terms of talc content [21]. Cumulative yields of the froth product, the content of talc in the cumulative froth product at the three different flotation times (τ), and content of talc in the feed (α) were then used to calculate the recovery of talc (R t using Equation (1)) and gangue minerals (R g using Equation ( 2)) to the froth product (talc concentrate) as follows:…”
Section: Separation Efficiencymentioning
confidence: 99%
See 1 more Smart Citation